Cold Hardiness of Primary Buds of Wine and Table Grape Cultivars in Poland - Lisek, J.; Lisek, A. (South African Journal of Enology and Viticulture, 2020)
The aim of this study was to compare the cold resistance of grapevine cultivars in field conditions. Following the winters of 2016/2017 and 2017/2018, an assessment of frost damage was carried out on the vines of 42 wine cultivars and 45 table grape cultivars grown in central Poland (Skierniewice, latitude 51.9627 N, longitude 20.1666 E). The minimum temperature for each of the two winters was recorded on 2017-01- 07 (-20.9°C) and on 2018-02-27 (-20.1°C). Among the assessed cultivars, 19 (13 wine grape cultivars and six table grape cultivars) belonged to V. vinifera species and 68 were inter- or inter-intraspecific hybrids. Cultivars were divided into five classes of different frost tolerance, with information on the proportion of primary buds frozen given in the brackets: very resistant (below 1.9%), resistant (2% to 24.9%), medium susceptible (2% to 74.9%), susceptible (75% to 95.9%) and very susceptible (above 96%). The number of wine and table grape cultivars in particular classes (mean for two winters) was as follows: very resistant – 20 (wine) and 10 (table), resistant – 15 and 13, medium susceptible – six and 20, susceptible – one and two. Both the V. vinifera cultivars and the interspecific hybrids were highly diversified in terms of frost tolerance. In most cultivars, the number of frozen buds after the winter of 2016/2017 was greater than after the winter of 2017/2018. Among V. vinifera, ‘Riesling’, ‘Pinot Noir’, ‘Chasselas Dore’ (reference) and ‘Tauberschwarz’, ‘Veltliner Frührot’ (‘Fruehroter Malvasier’), ‘Turan’, ‘Domina’, ‘Tressot Panache’, ‘Blue from Tychy’, and ‘Irsai Oliver’ were very resistant or resistant. Other cultivars of V. vinifera were medium susceptible or susceptible.